THE BEAMS’ VIBRATIONS SIMULATION OF RAILWAY BRIDGES IN THE SPHERE OF OBJECT - ORIENTED SOFTWARE “DELPHI” - Raspopov, O. S.; Artyomov, V. Ye.; Rusu, S. P. (Science and Transport Progress, 2010)
The basic stages of development of the program complex for calculation of statics and dynamics of the rod and beam constructions of railway bridges based on combining the finite-element method and the equations of solid dynamics are described.